The Effectiveness Of Angiotensin Receptor Neprilysin Inhibitor On Improving The Cardiac Remodelling Compared To Ace-Inhibitor On Patients With Chronic Heart Failure - Maulana, Muhammad Sobri (Indonesian Journal of Pharmaceutical and Clinical Research, 2021)
Heart failure is one of the major cause of patientâ€™s admittance to the hospital. Primary hypertension is one of the most universal comorbidities that precedes heart failure and is one of the more common risk factors held by the majority of the population. Right now, antihypertension that are generally used is from Angiotensin-Converting Enzyme Inhibitor (ACE-I) and Angiotensin Receptor Blocker (ARB). A new group of an antihypertensive agent called â€œAngiotensin Receptor Neprilysin Inhibitor (ARNI)â€ to further improve the patient condition. This study aims to evaluate the effectivity of ARNI against ACE-I regarding its cardiac reverse remodeling effect. Search strategy was done using electronic databases, which are Pubmed, Scopus, and Cochrane. Articles included are therapeutic study that is in line with the clinical question and fulfills the inclusion and exclusion criteria. Critical appraisal was done by assessing the articleâ€™s validity, importance, and applicability according to Oxford Center of Evidence-Based Medicine 2011 to two chosen articles. 2 articles are chosen and appraised. Both of the study are shown to be valid and shows that ARNI has a significantly better result on improving cardiac reverse remodeling via the left ventricle ejection fraction compared to ACE-I. However, the applicability of ARNI is still debatable in Indonesia as it was not covered by national insurance and there is no generic form. ARNI shows to be significantly better to reverse cardiac remodeling compared to ACE-I, but its applicability has to be improved to be implemented in Indonesia.